Effects of Cognitive Load on Pure-Tone Audiometry Thresholds in Younger and Older Adults. Issue 4 (July 2020) - Heinrich, Antje; Ferguson, Melanie A.; Mattys, Sven L.
Abstract : Objectives: Cognitive load (CL) impairs listeners' ability to comprehend sentences, recognize words, and identify speech sounds. Recent findings suggest that this effect originates in a disruption of low-level perception of acoustic details. Here, we attempted to quantify such a disruption by measuring the effect of CL (a two-back task) on pure-tone audiometry (PTA) thresholds. We also asked whether the effect of CL on PTA was greater in older adults, on account of their reduced ability to divide cognitive resources between simultaneous tasks. To specify the mechanisms and representations underlying the interface between auditory and cognitive processes, we contrasted CL requiring visual encoding with CL requiring auditory encoding. Finally, the link between the cost of performing PTA under CL, working memory, and speech-in-noise (SiN) perception was investigated and compared between younger and older participants. Design: Younger and older adults (44 in each group) did a PTA test at 0.5, 1, 2, and 4 kHz pure tones under CL and no CL. CL consisted of a visual two-back task running throughout the PTA test. The two-back task involved either visual encoding of the stimuli (meaningless images) or subvocal auditory encoding (a rhyme task on written nonwords). Participants also underwent a battery of SiN tests and a working memory test (letter number sequencing). Results: Younger adults showed elevated PTA thresholds under CL, but only when CL involved subvocal auditory encoding. CL had no effect when it involved purely visual encoding. In contrast, older adults showed elevated thresholds under both types of CL. When present, the PTA CL cost was broadly comparable in younger and older adults (approximately 2 dB HL). The magnitude of PTA CL cost did not correlate significantly with SiN perception or working memory in either age group. In contrast, PTA alone showed strong links to both SiN and letter number sequencing in older adults. Conclusions: The results show that CL can exert its effect at the level of hearing sensitivity. However, in younger adults, this effect is only found when CL involves auditory mental representations. When CL involves visual representations, it has virtually no impact on hearing thresholds. In older adults, interference is found in both conditions. The results suggest that hearing progresses from engaging primarily modality-specific cognition in early adulthood to engaging cognition in a more undifferentiated way in older age. Moreover, hearing thresholds measured under CL did not predict SiN perception more accurately than standard PTA thresholds. Abstract : Supplemental Digital Content is available in the text.